Description and phylogenetic classification of Stackelberginia cerberus sp. nov. (Diptera: Asilidae), comprising the first record of this genus from the Nearctic - Mcknight, Tristan A.; Cannings, Robert A. (Zootaxa, 2017)
Stackelberginia cerberus sp. nov. (Diptera: Asilidae) is described from the Amargosa desert (USA: Nevada) and compared to related taxa. This is the first record of the genus in the Western Hemisphere; other species live in the deserts of central Asia. Stackelberginia Lehr is proposed as the sister taxon to Lasiopogon Loew in the subfamily Stichopogoninae based on morphological characters and a Bayesian species tree estimated from one mitochondrial (COI) and three nuclear protein-coding loci (AATS, PEPCK, wingless). Stackelberginia has the medially divided epandrium and rotated hypopygium of Lasiopogon, but the facial gibbosity is flat, macrosetae of thorax, head, and legs are unusually long, and phenology peaks in late autumn.